As desigualdades econômicas regionais e o setor agropecuário do Rio Grande do Sul - Batista, Inajara Martins (2006)
From the viewpoint of economic development, the state of Rio Grande do Sul presents a particularly special kind of peculiarity, when taking into account the state divided into two regions: North and South. The Southern half, which used to have the state s economical power, began a process of economical stagnation in the midst of the XX century, which persists until today. The Northern half, which used have the least economical power, is now considered the state s most economically developed region. This process has had continuity due to the economical concentration that can be observed in a certain region of the Northern half, referred to by Alonso et al. (1994) as the Northeastern region. Thus, this work considers the state of Rio Grande do Sul divided into three regions: Northeastern, Northern and Southern regions. Many factors have contributed to this economical condition, but it is prominently due to the processes of occupation, urbanization and industrialization. The importance of the agricultural sector in the state of Rio Grande do Sul is known; it is also known that these regional disparities, as they become increasingly accentuated, have a direct effect on the activities performed by this sector. The North-eastern Region, which s size corresponds to only 8.98% of the total area of the state, represents 53.44% of the state Gross National Product (GNP) and 15.53% of the Gross Agricultural Value (GAV). However, in economic values per area, the region contributes more than the Southern and Northern regions which correspond to approximately 87% of the state area contribute to 84.47% to the state s GAV. The Northern Region perceivably presents some advantages over the other two regions, being that there is a better-structured consumer market, with higher acquisitive power; the agricultural activities performed are more dynamic and there are better opportunities for industrialization and commerce which differs outstandingly from the Southern and Northern regions. From this analysis, the importance of the study of the dynamics of this process can be verified, so that other efficient policies can be elaborated in order to minimize the effects of regional economical disparities on the Agricultural sector of Rio Grande do Sul state.